Numerical investigation of self-pulsation for narrow stripe A1GaAs/GaAs and InGaAsP/InP semiconductor laser diodes - O'Brien, Canice G. (Trinity College (Dublin, Ireland). School of Physics, 2004)
Self-pulsation in laser diodes is the process by which pulsed light is emitted from the laser while under direct current injection. As a result of their low relative intensity noise under feedback conditions, and high frequency pulsed emission, they are of great interest due to their current and potential future applications in telecommunications systems as well as optical data storage applications.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin